Junb controls lymphatic vascular development in zebrafish via miR-182 - Kiesow, Kristin; Bennewitz, Katrin; Cramer-Stoll, Sandra; Kroll, Jens (Scientific reports, 2015)
JUNB, a subunit of the AP-1 transcription factor complex, mediates gene regulation in response to a plethora of extracellular stimuli. Previously, JUNB was shown to act as a critical positive regulator of blood vessel development and homeostasis as well as a negative regulator of proliferation, inflammation and tumour growth. Here, we demonstrate that the oncogenic miR-182 is a novel JUNB target. Loss-of-function studies by morpholino-mediated knockdown and the CRISPR/Cas9 technology identify a novel function for both JUNB and its target miR-182 in lymphatic vascular development in zebrafish. Furthermore, we show that miR-182 attenuates foxo1 expression indicating that strictly balanced Foxo1 levels are required for proper lymphatic vascular development in zebrafish. In conclusion, our findings uncover with the Junb/miR-182/Foxo1 regulatory axis a novel key player in governing lymphatic vascular morphogenesis in zebrafish.
Gesehen am 15.03.2018